2009
DOI: 10.1002/app.30442
|View full text |Cite
|
Sign up to set email alerts
|

Covalent immobilization of α‐amylase onto UV‐curable coating

Abstract: A UV-curable N-(4-sodiumsulfophenyl)maleimide monomer was synthesized, and its potential for enzyme binding was investigated. The bromine, which is used to activate the synthesized monomer for covalent attachments, has the advantage of giving reaction with the surface groups of enzyme under very mild conditions (0 C, 30 min). In this procedure, sulfonyl bromide pendant monomer reacted with amino groups of the protein to form sulfonamide bonds. Polymeric support was prepaped by UVcuring technique. The water ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…There are several studies including α‐amylase immobilization in which the binding capacity of the support materials is labile due to the characteristic properties of the prepared materials. In our previous studies, on α‐amylase immobilization capacities onto amine functionalized glass beads,16 UV curable N‐(4‐sulfophenyl)‐maleimide polymeric films,17 glutaraldehyde activated silanized calcium carbonate were reported18 as 25.2, 68.18, and 199.43 mg/g support material, respectively. In this study, the amount of the covalently bonded enzyme was found to be as 181.48 ± 3.60 mg/g of hybrid nanofiber.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies including α‐amylase immobilization in which the binding capacity of the support materials is labile due to the characteristic properties of the prepared materials. In our previous studies, on α‐amylase immobilization capacities onto amine functionalized glass beads,16 UV curable N‐(4‐sulfophenyl)‐maleimide polymeric films,17 glutaraldehyde activated silanized calcium carbonate were reported18 as 25.2, 68.18, and 199.43 mg/g support material, respectively. In this study, the amount of the covalently bonded enzyme was found to be as 181.48 ± 3.60 mg/g of hybrid nanofiber.…”
Section: Resultsmentioning
confidence: 99%
“…The immobilized enzyme had excellent operational stability, the activity of which remained above 80% of the initial state after 15th use. In our previous study, it was found that the reuse capabilities of α‐amylase were in the range of 78–85% when immobilized on UV curable N‐(4‐sulfophenyl)‐maleimide polymeric films17 and %75 when immobilized on functionalized glass beads 16…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, it was found that free enzyme lost its activity completely within the 15 days [38,39]. The results clearly showed that immobilized amylase preserved its activity for a longer time than the free one [40]. Reuse capability of the immobilized enzyme was examined by recording the changes in activity after repeated washes.…”
Section: Effect Of Storage and Reusability On Activity Of Immobilizedmentioning
confidence: 98%
“…One of the biggest challenges in designing a new enzymebased biosensor is to find the optimal balance between stability and activity of the enzyme. Immobilization methods, such as cross-linking bonding (Jung and Paradiso 2009), covalent attachment (Drevon et al 2002), polymer inclusion (Umran and Memet 2009) and simple adsorption, have different effectiveness with regard to the stability of the signal generated, due to the fact that a higher or lower percentage of enzyme immobilized is lost during the measurement. On the other hand, better stability is generally obtained, paying the price of the loss of signal intensity related to a lower enzyme catalytic activity.…”
Section: Introductionmentioning
confidence: 99%